Adsorption of Acetic Acid, Cadmium ions, Lead ions and Iodine Using Activated Carbon from Waste Wood and Rice Husks - TO Goodhead; KK Dagde (Journal of Applied Sciences and Environmental Management)
This paper presents the performance evaluation of locally prepared activated carbon from rice husk and saw dust. The raw materials were carbonized at different temperatures (600-800oC) using sodium hydroxide (NaOH) as the activating agent. The study includes moisture content determination of the raw materials used in the activation and carbonization processes. The effects of variations in carbonization temperature and concentration of activating agent on various performance indices for good quality absorbent were investigated. The percentage yield of the activated carbon from the raw materials as well as iodine number and adsorption of heavy metals from aqueous solutions were also determined. The experimental data which make a comparative assessment of activated carbon obtained from rice husk and saw dust were also presented. Preliminary examination of the raw materials showed that rice husk and saw dust had a moisture content of 14.6% and 5.8% respectively. Increase in carbonization temperature decreases yield of the active carbon. The highest yield of about 48% was obtained from rice husk at 600oC, with moisture content of 26%. The rice husk at 800oC gave a yield of 47.2% with moisture content of 26.5%. While the yields of the saw dust were 44% at 600oC and 40% at 800oC with moisture content of 17% and 19% respectively. A detailed study of mass transfer processes indicated that activated carbon from these materials show good performance. @JASEM